2018
DOI: 10.3390/en11123427
|View full text |Cite
|
Sign up to set email alerts
|

Design and Implementation of an IoT System for Smart Energy Consumption and Smart Irrigation in Tunnel Farming

Abstract: Efficient and cost effective ways of irrigation have emerged as the need of the hour due to limited sweet water resources, especially the countries that are seriously hit by a lack of sweet water reservoirs. The majority of the water is wasted due to inefficient ways of watering plants. In this paper, we propose an intelligent approach for efficient plant irrigation that has a database of daily water needs of a type of plant and decides the amount of water for a plant type on the basis of the current moisture … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(42 citation statements)
references
References 29 publications
(45 reference statements)
0
42
0
Order By: Relevance
“…Table 4 lists the cloud platforms that have been used in the reviewed articles. [14,32,41,50,64,72,77,78,88,99,110,113,114,119,121,132,142,[151][152][153]156,169,175,197] Thingspeak [44,56,98,115,118,130,143,146,158,160,166,170,173,191] The rest of the articles where the authors identify the storage system utilize databases. As it can be seen in Figure 28, in 12 articles the information is stored in a database, but the name of the employed database is not specified.…”
Section: Cloud Platformsmentioning
confidence: 99%
See 2 more Smart Citations
“…Table 4 lists the cloud platforms that have been used in the reviewed articles. [14,32,41,50,64,72,77,78,88,99,110,113,114,119,121,132,142,[151][152][153]156,169,175,197] Thingspeak [44,56,98,115,118,130,143,146,158,160,166,170,173,191] The rest of the articles where the authors identify the storage system utilize databases. As it can be seen in Figure 28, in 12 articles the information is stored in a database, but the name of the employed database is not specified.…”
Section: Cloud Platformsmentioning
confidence: 99%
“…Other authors have identified the utilized databases. The most utilized one is MySQL [35,46,54,58,67,76,96,110,124,126,144,158] 12 papers, followed by SQL [69,119] [14,32,41,50,64,72,77,78,88,99,110,113,114,119,121,132,142,[151][152][153]156,169,175,197] Thingspeak [44,56,98,115,118,130,143,146,158,160,166,170,…”
Section: Cloud Referencesmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, many agriculture researchers apply WSNs to monitor environmental criteria [2][3][4][5][6]. In addition to standard environmental conditions such as temperature, humidity, and precipitation, data such as the ability to control the water level or temperature level are the subject of research in an agricultural environment [10].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, regarding water management in crops, which is the scope of this work, several approaches have been proposed in literature making a proper use of IoT technology for developing smart irrigation systems, some of them based on the use of FIWARE as well. In [27], an IoT system for smart energy consumption and irrigation was presented. The system decides the amount of water required by the crops according to the current moisture in soil and humidity (measured by mean of IoT sensors) and the time of the day.…”
Section: Introductionmentioning
confidence: 99%